(untitled) (INNOTEC, 2024)
The effect of extreme water level decreases on the reproduction of migratory fish in the Uruguay River was evaluated. Extreme water decreases have a negative effect on ichthyoplankton and provide new insights into the intensity of this effect during consecutive drought periods. The study compares the abundance and composition of ichthyoplankton during three consecutive reproductive periods (October-March) during extreme water level decreases in the river from 2020-2023, with data from the previous 10 years (2010-2020) through weekly samplings at four sites within the Salto Grande reservoir. Compared to the previous decade, decreases in the abundances of P. lineatus (60-85 %), Pseudoplatystoma spp. (52-79 %), L. patí (39-82 %), Pimelodus spp. (24-61 %), and Anostomidae (26-56 %) were observed, as well as temporal changes in ichthyoplankton density. Unlike the previous period (2010-2020), where harmful cyanobacteria blooms developed during summer droughts, during the extraordinary period caused by a hydrological phenomenon, no cyanobacteria bloom events were recorded. The absence of this harmful effect, combined with the resilience of fish observed during the previous period, generates reasonable expectations that at the end of the extraordinary period, fish will slowly recover their previous reproductive activity.